2018
DOI: 10.5194/wes-2017-59
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wind tunnel experiments on wind turbine wakes in yaw: Effects of inflow turbulence and shear

Abstract: Abstract. The wake characteristics behind a yawed model wind turbine exposed to different customized inflow conditions are investigated. Laser Doppler Anemometry is used to measure the wake flow in two planes at x/D=3 and x/D=6 while the turbine yaw angle is varied from γ = [−30• , 0The objective is to assess the influence of grid-generated inflow turbulence and shear on the mean and turbulent flow components.The wake flow is observed to be asymmetric with respect to negative and positive yaw angles. A counter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Together with the inflow-dependent wake flow measurements on the same experimental setup presented in Bartl et al (2018), this study completes the link between detailed wake flow characteristics and power, yaw moments and thrust forces on a turbine operated in the wake.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Together with the inflow-dependent wake flow measurements on the same experimental setup presented in Bartl et al (2018), this study completes the link between detailed wake flow characteristics and power, yaw moments and thrust forces on a turbine operated in the wake.…”
mentioning
confidence: 96%
“…In this experiment T2 is controlled to its optimum power point, which strongly varies for different positions and upstream turbine operational parameters. The exact geometry and detailed performance curves of T1 are described in Bartl et al (2018), while T2's characteristics can be found in Bartl and Saetran (2017). In contrast to most other turbines, the investigated model turbines rotate counter-clockwise.…”
Section: Wind Turbine Modelsmentioning
confidence: 99%
See 3 more Smart Citations